Anti-Ri paraneoplastic syndrome associated with ophtalmoplegia, blepharospasm and palilalia - Martinaud, O; Guegan-Massardier, E; Iasci, L; Miret, N; Mihout, B; Hannequin, D (Revue neurologique, 2005)
Anti-Hu and anti-Yo are the most well-known anti-neuronal antibodies. The anti-Ri antibodies, which are less common, are generally found in subjects with opsoclonus-myoclonus, often associated with breast cancer. A 54-year-old woman presented anti-Ri antibodies associated with a paraneoplastic syndrome and unusual symptoms of ophthalmoplegia, blepharospasm, palilalia and ataxia. Adenocarcinoma of the breast was also found. After chemotherapy, radiotherapy, and several immunoglobulin infusions, the patient did not improve ten months after tumor surgery. Anti-Ri antibodies associated with paraneoplastic syndrome can be observed in patients who develop a rapidly progressive brainstem tumor. Breast or lung cancer and conduct to search a breast or pulmonary cancer.